Leroy Pope Walker correspondence - Walker, Leroy Pope, 1817-1884.
ALS written by Walker to thank Samuel Wylie Crawford for some newspaper articles in which Walker was mentioned.
Confederate secretary of war, army officer, and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Crawford, Samuel Wylie, -- 1827-1892 -- Correspondence; Army officers, Confederate; Cabinet officers -- Confederate States of America; Lawyers